Flame Atomic Absorption Spectrometric Determination of Gold, Palladium and Platinum in Catalytic Converters - Soylak, Mustafa; B. Buyuksekerci, Emel; Elci, Latif (Asian Journal of Chemistry, 2016)
A simple procedure for the flame atomic absorption spectrometric determination of gold, palladium and platinum contents of the catalytic converters of the automobiles was proposed in the present work. The procedure includes the combination of solid phase extraction of gold, palladium, platinum on amberlite XAD-7 adsorption resin and flame atomic absorption spectrometric determination. The procedure was also applied to the determination of analyte contents of natural waters with satisfactory results.